Culturally Relevant Health Care: A View Based on Intercultural Communicative Competence - Henríquez, Felipe; Abd-El-Kader, Giorgia; Marilao, Margarita (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
The intercultural nature of health care requires strategies that give priority to effectiveness within interactions such as communication. This article emphasizes communication in a health context –in particular intercultural communicative competence–as a tool for culturally relevant health care, mentioning some important variables for effectiveness and adaptation in intercultural situations. In the same way, diversity and cultural competence and their relation to health care are highlighted. Finally, some questions are exposed concerning culturally relevant health care.